Peran Institusi Penerima Wajib Lapor Dalam Dalam Menerima Laporan Pecandu Narkotika - Lubis, Muhammad Ansori; Rahmadani, Gema (JUNCTO: Jurnal Ilmiah Hukum, 2024)
The purpose of this study is to analyze the Factors Causing Parents or Guardians of Narcotics Addicts Not to Report to the Institution of Compulsory Reporting (IPWL), and to evaluate the efforts made by institutions such as the National Narcotics Agency (BNN) in Increasing Community Participation to Report to IPWL. This study uses normative juridical and descriptive-analytical methods, with legal data and in-depth interviews. The data were analyzed qualitatively to evaluate the implementation of the mandatory reporting policy and its impact on the rehabilitation of addicts. The results provide recommendations for policy improvement. The results of the study show that the barriers to parents reporting to IPWL involve psychological, social, and lack of information. Holistic solutions, such as awareness raising, stigma reduction, and rehabilitation services, are expected to encourage more families to report back. BNN's efforts through socialization, family empowerment, counseling, and community-based service development reflect a strong commitment to dealing with narcotics problems. Cooperation between various parties is still needed to create a drug-free future.